AI DEPENDENCY AND INDEPENDENT LEARNING: A SEQUENTIAL EXPLANATORY MIXED-METHODS ANALYSIS OF STUDENTS’ PERCEPTIONS IN ENGLISH LANGUAGE EDUCATION - Elis Suminar; Slamet Asari (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT The advancement of Artificial Intelligence (AI) technology has driven significant changes in how students learn English, particularly in relation to the potential emergence of dependency on such technologies. AI tools such as grammar checkers, machine translation, and generative text platforms assist students in understanding materials and improving their language skills independently. This study aims to examine students’ perceptions of their dependency on AI in supporting independent English language learning. This research employs a mixed-methods approach, collecting data through questionnaires administered to 30 EFL students and semi-structured interviews with five purposively selected participants. The findings indicate that students appreciate the use of AI tools such as Grammarly, Google Translate, and ChatGPT for providing instant feedback, personalized learning experiences, and improved language proficiency. On the other hand, the findings also reveal a tendency toward dependency, which may reduce learners’ initiative in independent study if not properly managed. The study concludes that the use of AI can effectively support learner autonomy when applied responsibly, strategically, and in balance with conventional learning methods. This study provides insights for educational stakeholders in leveraging AI to promote independent learning and digital literacy. ABSTRAK Kemajuan teknologi Kecerdasan Buatan (Artificial Intelligence/AI) telah mendorong perubahan signifikan dalam cara mahasiswa mempelajari bahasa Inggris, khususnya terkait potensi munculnya ketergantungan dalam penggunaan teknologi tersebut. Alat-alat AI seperti pemeriksa tata bahasa, penerjemah otomatis, dan platform pembuat teks generatif membantu mahasiswa memahami materi serta meningkatkan keterampilan bahasa secara mandiri. Penelitian ini bertujuan untuk mengkaji persepsi mahasiswa terhadap ketergantungan mereka pada AI dalam mendukung pembelajaran bahasa Inggris secara mandiri. Penelitian ini menggunakan pendekatan metode campuran dengan pengumpulan data melalui kuesioner terhadap 30 mahasiswa EFL dan wawancara semi-terstruktur dengan lima partisipan yang dipilih secara purposif. Hasil penelitian menunjukkan bahwa mahasiswa mengapresiasi penggunaan alat AI seperti Grammarly, Google Translate, dan ChatGPT karena mampu memberikan umpan balik instan, pengalaman belajar yang terpersonalisasi, serta peningkatan kemampuan bahasa. Di sisi lain, temuan juga menunjukkan adanya kecenderungan ketergantungan yang berpotensi mengurangi inisiatif belajar mandiri apabila tidak dikontrol dengan baik. Simpulan penelitian ini menegaskan bahwa pemanfaatan AI dapat secara efektif mendukung kemandirian belajar mahasiswa apabila digunakan secara bijak, terarah, dan diimbangi dengan strategi pembelajaran konvensional. Penelitian ini memberikan wawasan bagi pemangku kepentingan pendidikan dalam memanfaatkan AI untuk mendorong kemandirian belajar dan literasi digital.